Association between health service use and diarrhoea management approach among caregivers of under-five children in Nepal - Ghimire, Pramesh Raj (PLoS One, 2018)
INTRODUCTION: Diarrhoea among children under-five is a serious public health problem in many developing countries, including Nepal. This study aimed to examine the association between health service utilization and diarrhoea management approaches among children under-five years in Nepal. METHODS: The combined 2001, 2006 and 2011 Nepal Demographic and Health Survey (NDHS) data sets were examined and the sample included 2,655 children aged 0–59 months who had diarrhoea 2-weeks prior to the each survey. Multilevel logistic regression analyses that adjust for clustering and sampling weight were used to examine the association between health service utilization and diarrhoea management approaches (Oral Rehydration Solution, increased fluids and/or continued feeding). RESULTS: The prevalence of extra fluids decreased significantly from 27% in 2001 to 15% in 2011 while that of ORS increased significantly from 32% in 2001 to 40% in 2011. The prevalence of continued feeding fluctuated between 83–89%. Multivariate analysis revealed that caregivers whose children received treatment or advice from health care providers during diarrhoea were 5.78 times more likely to treat diarrhoea with Oral Rehydration Solution (ORS) [adjusted Odds Ratio (aOR) 5.78, 95% confidence interval (CI) 4.50, 7.44], 1.56 (aOR 1.56, 95% CI 1.19, 2.05) times more likely to offer extra fluids, and 2.25 (aOR 2.25, 95% CI 1.50, 3.39) times more likely to use continued feeding than those who did not seek advice. CONCLUSIONS: Our findings indicate that health service utilization significantly improves diarrhoea management among under-five children. However, a broader national diarrhoeal disease control program to further reduce diarrhoea related morbidity and mortality in Nepal should focus on educating caregivers about the importance of the use of ORS as well as increase fluid intake to children under-five years with diarrhoea.